The N6-Methyladenosine Modification and Its Role in mRNA Metabolism and Gastrointestinal Tract Disease - Cai, Teng; Atteh, Lawrence Lawer; Zhang, Xianzhuo; Huang, Chongfei; Bai, Mingzhen; Ma, Haidong; Zhang, Chao; Fu, Wenkang; Gao, Long; Lin, Yanyan; Meng, Wenbo (Frontiers in Surgery, 2022)
The N6-methyladenosine (m6A) modification is the most abundant internal modification of messenger RNA (mRNA) in higher eukaryotes. Under the actions of methyltransferase, demethylase and methyl-binding protein, m6A resulting from RNA methylation becomes dynamic and reversible, similar to that from DNA methylation, and this effect allows the generated mRNA to participate in metabolism processes, such as splicing, transport, translation, and degradation. The most common tumors are those found in the gastrointestinal tract, and research on these tumors has flourished since the discovery of m6A. Overall, further analysis of the mechanism of m6A and its role in tumors may contribute to new ideas for the treatment of tumors. m6A also plays an important role in non-tumor diseases of the gastrointestinal tract. This manuscript reviews the current knowledge of m6A-related proteins, mRNA metabolism and their application in gastrointestinal tract disease.